SIMULATION OF PRESSURE REDUCING VALVE (PRV) INSTALLATION IN THE DISTRIBUTION NETWORK (CASE STUDY: NORTHERN REGION OF SUMBER IPA PALUKAHAN PDAM PADANG CITY) - Adetya, Ashifa; Dewi, Nadia Tripermata; Komala, Puti Sri (Jurnal Reka Lingkungan, 2023)
ABSTRAKPenelitian ini bertujuan untuk mensimulasikan lokasi pemasangan Pressure Reducing Valve (PRV) yang tepat  pada jaringan perpipaan di Wilayah utara Perumda Air Minum (PDAM) Kota Padang menggunakan satu sumber air. Simulasi hidrolis menggunakan aplikasi EPANET serta data sekunder dari PDAM Padang. Data yang dibutuhkan untuk simulasi terdiri dari data debit reservoir, pelanggan wilayah utara, serta perpipaan. Hasil simulai EPANET kemudian dibandingkan dengan hasil pengukuran lapangan. Terdapat perbedaan tekanan yang cukup signifikan antara simulasi EPANET dengan hasil pengukuran lapangan. Tingginya tekanan hasil simulasi, karena sumber air IPA Palukahan yang memiliki perbedaan elevasi yang besar dengan daerah pelayanan. Pemasangan Pressure Reducing Valve (PRV) merupakan pilihan untuk mengurangi tekanan pada jaringan pipa sampai batas tertentu. Dalam simulasi lokasi pemasangan PRV yang tepat di jaringan distribusi ditentukan agar tekanan di daerah pelayanan yang diperoleh memenuhi persyaratan. Rekomendasi penempatan PRV antara Node 119 dan Node 120 pada ketinggian 30 mdpl. PRV dapat menurunkan tekanan dari 1,9 atm – 10,7 atm menjadi 1,2 atm – 6,9 atm. Pemasangan PRV dapat menjadi langkah awal dalam persiapan pembentukan DMA (District metered Area) di wilayah utara kota Padang dalam rangka menurunkan tingkat kebocoran air.Kata kunci: EPANET, Instalasi Pengolahan Air (IPA) Palukahan, Jaringan distribusi, Pressure Reducing Valve (PRV), TekananABSTRACTThis study aims to simulate the exact location of the Pressure Reducing Valve (PRV) installation in the pipeline network in the northern area of the Municipal Water Supply Company (PDAM) of Padang City using one water source. The water source used is Palukahan Water Treatment Plant (WTP) which has a relatively high elevation to the service area. The hydraulic simulation used the EPANET and secondary data from PDAM Padang. The data needed for the simulation consists of reservoir discharge data, northern customers, and piping. The results of the EPANET simulations were then compared with the results of field measurements. There is a significant difference in pressure between the EPANET simulation and the field measurement results. The high pressure from the simulation results is due to the Palukahan WTP water source which has a large elevation difference from the service area. Installation of a Pressure Reducing Valve (PRV) is an option to reduce the pressure in the pipe network to a certain extent. In the simulation, the appropriate PRV installation location in the distribution network is determined so that the pressure in the service area obtained meets the requirements. Recommended PRV placement between Node 119 and Node 120 at an altitude of 30 meters above sea level. PRV can reduce pressure from 1.9 atm – 10.7 atm to 1.2 atm – 6.9 atm. Installing PRV can be the first step in preparing for the formation of a DMA in the northern area of Padang City in order to reduce the level of water leakage.Keywords: EPANET, Palukahan Water Treatment Plant (WTP), Distribution Network, Pressure Reducing Valve (PRV), Padang Water Utility (PDAM Padang), Pressure